THE DIFFICULTIES OF INSTITUTIONALIZATION OF RELATIONS „CENTRE– REGIONS” IN UKRAINE - Кукарцев, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
Some problems of formation and functioning of political institutes in system of state center relations with subnational territories of regional level in Ukraine are researched. The politico-legal status of regional authorities and difficulties of political representation of regions on national level ensuring are viewed. The connection of institutionalization’s process of „centre – regions” relations with process of state territorial integration is analyzed.